2015
DOI: 10.17051/io.2015.10038
|View full text |Cite
|
Sign up to set email alerts
|

Mesleki Gelişim: Öğrenen olarak Öğretmen Eğitimcileri

Abstract: ABSTRACT. This study outlines the professional development of teacher educators. More specially, teacher educators' descriptions and definitions of professional development and their participating professional development activities are examined. Further, to what extent teacher educators develop themselves in the professional sense, and supports and obstacles are explored. Within a case design, fourteen teacher educators were interviewed. Data were triangulated with annual performance reports. Findings point t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…Actually, in the previous studies, it was emphasized that teachers 'must be a model for educational stakeholders in developing national and universal values' (MEB, 2008); 'must be an ethic leader model in the classroom' (Lehr, 2003); 'must be an efficient model to teach values' (Çetingöz, 2015). In a study conducted by Vidovic and Velkovski (2013) it was expressed that teachers must have personal values such as collaboration, sharing developments in the field with colleagues and renewing oneself; in another study conducted by Boydak-Özan, Polat, and Şener (2014) the findings show that teachers must follow up on publications on innovations about their areas; in the researches of Gökmenoğlu, Beyazova, and Kılıçoğlu (2015), NCATE ( 2006), Uştu, Taş-Mentiş, and Sever (2016) the findings revealed that the teachers should have professional values in the form of sharing and solidarity. In the studies conducted by Çubukçu et al (2012), Işıktaş (2015), Sezer (2016), it was mostly emphasized that teachers should have leadership skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, in the previous studies, it was emphasized that teachers 'must be a model for educational stakeholders in developing national and universal values' (MEB, 2008); 'must be an ethic leader model in the classroom' (Lehr, 2003); 'must be an efficient model to teach values' (Çetingöz, 2015). In a study conducted by Vidovic and Velkovski (2013) it was expressed that teachers must have personal values such as collaboration, sharing developments in the field with colleagues and renewing oneself; in another study conducted by Boydak-Özan, Polat, and Şener (2014) the findings show that teachers must follow up on publications on innovations about their areas; in the researches of Gökmenoğlu, Beyazova, and Kılıçoğlu (2015), NCATE ( 2006), Uştu, Taş-Mentiş, and Sever (2016) the findings revealed that the teachers should have professional values in the form of sharing and solidarity. In the studies conducted by Çubukçu et al (2012), Işıktaş (2015), Sezer (2016), it was mostly emphasized that teachers should have leadership skills.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Eisenschmidt and Löfström (2008) suggest that teaching profession needs to be able with communication skills, democratic skills, ability to design and having comprehensive knowledge of program, the appropriate teaching process, and ability to prepare suitable learning environments for children with special education need. In addition, ability to design materials and use technology are taking part in the findings of (Gökmenoğlu, Beyazova, & Kılıçoğlu, 2015;Işıktaş, 2015;Karabacak et al, 2015;Karabacak, 2016;Özcan, 2011;Sezer, 2016;Uştu, Taş-Mentiş, & Sever, 2016;Tunca, 2012); planning skill in the finding of (Arslan & Özpınar, 2008;Sezer, 2016). Moreover, in the studies conducted by Calderhead and Shorrock (1997), Montecinos and Nielsen (1997) it was revealed that the teachers must love the children, to improve the lives of children and to have responsibility for them.…”
Section: Discussionmentioning
confidence: 99%
“…Bazı çalışmalarda da nitelikli ve başarılı bir öğretim için öğretmenlerin mesleki bilgi, beceriler ve tutumlarına ilişkin yeterlikleri ile bilgi ve beceri düzeylerinin artırılmasının gerekliliğine inandıkları gösterilmiştir (Ekici, 2014;Koçak, Turan ve Aydoğdu, 2012;Mete ve Gürsoy, 2014). Öğretmenler mesleki gelişimi değişen koşullar ve teknolojilere ayak uydurma, bilgi ve beceriyi artırma, kendini yenileme ve güncel tutma olarak algılamakta ve bir gereklilik olarak görmektedir (Altun ve Vural, 2012;Ceylan ve Özdemir, 2016;Gökmenoğlu, Beyazova ve Kılıçoğlu, 2015;Boydak, Polat ve Şener, 2014;Uştu, Mentiş ve Sever, 2016). Erdağ ve Karadağ (2018) öğretmenlerin hesap verme duygularının aynı şekilde kıdem, eğitim düzeyi, branşları ve okul türüne göre farklılık göstermediğini, öte taraftan, cinsiyetin de benzer şekilde hesap verme duygularında fark yarattığını belirlemiştir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Ancak, bilgi toplumu ile yenilenen öğrenme ve öğretme süreçleri öğretmenlere karmaşıklık, öngörülemezlik ve belirsizlikler getirmiş, öğretmenlerin rollerini çeşitlendirmiş ve onlardan beklenenleri arttırmıştır. Böyle bir mesleki iklimde, öğretmenlerin daha etkin rol alarak süreci yönetebilmek için mesleki bilgi ve becerilerini geliştirmeye odaklanmaları son derece önemlidir (Day, 2007;Fullan, 2001).…”
Section: Introductionunclassified
“…The information society renewed with the learning and teaching processes brought teachers, complexity, unpredictability, uncertainties, diversified the roles of teachers, and increased expectations from them. In such a professional climate, it is crucial to focus on developing teachers' professional knowledge and skills to manage the process (Day, 2007;Fullan, 2001). Wilson (2013) defines effective professional development as content-oriented processes and activities ensuring the joint participation of teachers and administrators, consisting of school practices and policies, and having sufficient duration.…”
Section: Introductionmentioning
confidence: 99%